I'll be seeing you [large type] - Hatcher, Robin Lee (Thorndike Press large print Christian fiction series., 2022)
Brianna Hastings's life seemed dull until she was smitten by Greg, who leads an exciting, independent life-- the kind of life she longs for. For a college history assignment, Brianna has to interview her great-grandmother about life during World War II. During the interview, Daisy presses her with questions about Greg's character. What could her great-grandmother possibly know about love at first sight? The questions take both women back to Boise, Idaho, in the early 1940s, when war emphasized how fragile life could be. Daisy and her older sister pine for the same handsome bomber pilot-- until one night of terrible judgment forces Daisy to live a lie. Could what she learned about love save Brianna from heartache three generations later? -- adapted from back cover